PERAN INDONESIA SEBAGAI ANGGOTA INTERNATIONAL MARITIME ORGANIZATION (IMO) DALAM MENEGAKKAN KEAMANAN PELABUHAN MELALUI IMPLEMENTASI INTERNATIONAL SHIP AND PORT SECURITY CODE (ISPS CODE) DI INDONESIA - Frinandya Dewi Saputra (2021)
The research of this paper aims to understand Indonesia's role in port security applications as a member of the International Maritime Organization (IMO) board of directors through the implementation of the "International Ship and Port Security Code" in Indonesia. This research uses the concept of maritime security to analyze maritime threats related to port security, the concept of international organizations to analyze the role of IMO as an agency responsible for responding to maritime security threats and Indonesia's role in it, and the concept of international regime to analyze the ISPS Code as a solution to various maritime threats. In the analysis, the author uses a qualitative method (case studies) to provide descriptive answers based on existing facts. The data were collected by conducting interviews as primary data and literature study as secondary data. The author believes that Indonesia, as a member of the IMO, has a commitment and fulfills its responsibilities, which is reflected in the increase in waters, ports, and transportation safety (especially the implementation of ISPS rules), including general security and maritime environmental protection. The impact of the implementation of ISPS Code is improving good image of Indonesia's port security in international society.